Retinal dystrophins and the retinopathy of Duchenne muscular dystrophy - Barboni, Mirella Telles Salgueiro; Joachimsthaler, Anneka; Roux, Michel J.; Nagy, Zoltán Zsolt; Ventura, Dora Fix; Rendon, Alvaro; Kremers, Jan; Vaillend, Cyrille (Progress in Retinal and Eye Research, 2022)
Duchenne muscular dystrophy (DMD) is caused by X-linked inherited or de novo DMD gene mutations predominantly affecting males who develop early-onset muscle degeneration, severely affecting their quality of life and leading to reduced life expectancy. DMD patients may also develop proliferative retinopathy, cataract, ERG abnormalities, altered contrast sensitivity, color vision losses, and elevated flash detection thresholds during dark adaptation. Depending on the position of the genetic alteration in the large DMD gene, it is associated with a lack of the full-length dystrophin protein possibly with an additional loss of one or several other dystrophins, which are normally transcribed from internal promoters in retina and crystalline lens. During the last decades, the properties of the dystrophins have been characterized in patients with different genetic alterations and in genetic mouse models of DMD. The complex expression pattern of the dystrophins in photoreceptors, Müller glial cells and astrocytes, likely influences synaptic transmission, ionic balance and vascular integrity of the retina. However, the specific function of each retinal dystrophin remains largely unknown. This review describes the current knowledge on dystrophin expression, the putative molecular, structural, and physiological properties of retinal dystrophins, and the main clinical implications associated with the loss of dystrophins in DMD patients and mouse models. Current data and working hypotheses warrant future research on retinal dystrophins to increase our understanding of dystrophin function in the central nervous system in general and to unveil new retinal mechanisms and therapeutic avenues for retinal diseases.
CRIS-Team Scopus Importer:2022-12-02
Keywords: DMD gene; Duchenne and becker muscular dystrophy; Dystrophin; Electroretinogram; Gene therapy; Retina